Hemodynamic Response Alteration As a Function of Task Complexity and Expertise—An fNIRS Study in Jugglers - Carius, Daniel; Andrä, Christian; Clauß, Martina; Ragert, Patrick; Bunk, Michael; Mehnert, Jan (Frontiers in Human Neuroscience, 2016)
Detailed knowledge about online brain processing during the execution of complex motor tasks with a high motion range still remains elusive. The aim of the present study was to investigate the hemodynamic responses within sensorimotor networks as well as in visual motion area during the execution of a complex visuomotor task such as juggling. More specifically, we were interested in how far the hemodynamic response as measured with functional near infrared spectroscopy (fNIRS) adapts as a function of task complexity and the level of the juggling expertise. We asked expert jugglers to perform different juggling tasks with different levels of complexity such as a 2-ball juggling, 3- and 5-ball juggling cascades. We here demonstrate that expert jugglers show an altered neurovascular response with increasing task complexity, since a 5-ball juggling cascade showed enhanced hemodynamic responses for oxy-Hb as compared to less complex tasks such as a 3- or 2- ball juggling pattern. Moreover, correlations between the hemodynamic response and the level of the juggling expertise during the 5-ball juggling cascade, acquired by cinematographic video analysis, revealed only a non-significant trend in M1, indicating that a higher level of expertise might be associated with lower hemodynamic responses.